1984
DOI: 10.1136/bmj.289.6455.1350
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain after cholecystectomy.

Abstract: but a low titre to the porcine agent.3 Before operation a test dose was given to ascertain the therapeutic response and to detect side effects.4 In this case shivering, nausea, and back pain occurred but were rapidly relieved by oral chlorpheniramine. During the early postoperative period we gave 100 mg hydrocortisone and 10 mg chlorpheniramine intravenously before each infusion, later using chlorpheniramine alone. The platelet count remained unchanged. Altogether 270 000 units of porcine factor VIII were give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…The current study supports the data suggesting a link between cholecystectomy and MetS. This finding is in line with those of previous studies that reported a significant weight gain or elevation of glucose levels among cholecystectomized patients ( 3 , 27 ). Other studies showed that subjects with gall bladder disease or those who had undergone cholecystectomy had higher plasma TG levels, as well as higher levels of total cholesterol, but lower levels of HDL-C, than patients who had not undergone cholecystectomy ( 3 , 28 ).…”
Section: Discussionsupporting
confidence: 93%
“…The current study supports the data suggesting a link between cholecystectomy and MetS. This finding is in line with those of previous studies that reported a significant weight gain or elevation of glucose levels among cholecystectomized patients ( 3 , 27 ). Other studies showed that subjects with gall bladder disease or those who had undergone cholecystectomy had higher plasma TG levels, as well as higher levels of total cholesterol, but lower levels of HDL-C, than patients who had not undergone cholecystectomy ( 3 , 28 ).…”
Section: Discussionsupporting
confidence: 93%
“…An earlier study 28 reported a significant weight gain among cholecystectomized patients, with men and women gaining a mean of 4.6% and 3.3%, respectively, of their preoperative body weight at 6months after surgery. Other studies 27,29 that compared subjects with and without gallstones reported that, when compared with subjects without gallstones, the body mass index (BMI) and waist circumference of subjects with gallstones tended to be higher, and these differences were even more pronounced in cholecystectomized subjects ( Table 2).…”
Section: Cholecystectomy and Mets Componentsmentioning
confidence: 99%
“…It is possible that the observed positive association between obesity and postcholecystectomy may have been due to weight gain after cholecystectomy. 25,26 Caution is thus needed in interpreting the ®ndings regarding postcholecystectomy. Although rapid weight reduction is known to enhance gallstone formation, 27,28 much of the risk associated with weight loss or dieting has been ascribed to the underlying obesity or excess weight before dieting.…”
Section: Heaton Et Almentioning
confidence: 99%